Strategic Habitat Conservation for Declining Grassland Wildlife Populations in the Oaks and Prairies Joint Venture - James Giocomo; Johnathan Hayes; Kenneth Gee; Jeff Raasch; Robert Perez (National Quail Symposium Proceedings, 2017)
Degradation and conversion of functioning grassland ecosystems in North America has driven significant declines in grassland wildlife populations across multiple taxa. In an effort to address declines in the grasslands of Oklahoma and Texas, a number of governmental agencies and Non-Governmental Organizations have partnered to form the Oaks and Prairies Joint Venture (OPJV) to more strategically and collaboratively deliver conservation actions in this region. With northern bobwhite (Colinus virginianus) as the flagship species, OPJV has worked to implement a fully integrated Strategic Habitat Conservation framework that works at multiple scales to conduct biological planning, landscape conservation design, habitat tracking and population monitoring in support of conservation efforts aimed at restoring not just northern bobwhite, but a variety of bird and pollinator species that depend on healthy grasslands. The signature conservation delivery program of this effort was the Grassland Restoration Incentive Program (GRIP) which has improved habitat for grassland wildlife on over 24,300 hectares of working lands in focus areas throughout the OPJV geography since it was created in 2013. The Grassland Restoration Incentive Program was accompanied by a full complement of conservation delivery programs that support prescribed burning associations and other landowner cooperatives, utilize market-based conservation delivery strategies, and implement strategic outreach and communications. The conservation efforts were supported by over 4,500 point counts annually in National Bobwhite Conservation Initiative Coordination Implementation Program focal areas as well as 7 focal regions, each comprising clusters of 2-8 counties. Combining the efforts of multiple partners ties the range-wide population and habitat objectives with on-the-ground conservation actions for quail, other grassland birds, butterflies, and grassland pollinators.
Keywords: Colinus virginianus; habitat mangement; northern bobwhite; Joint Venture; population objective; grassland birds